Late-pregnancy anxiety as a distinct multidimensional construct: Psychometric evidence from a community-based sample - Nurul Jannah; Gunavathy Selvarajh (Institute of Computer Science (IOCS), 2026)
Anxiety during pregnancy was recognized as a common maternal mental health concern with important implications for maternal well-being and perinatal outcomes. Evidence suggested that anxiety experienced in late pregnancy was more context-specific and qualitatively distinct from general anxiety, yet its underlying structure remained insufficiently examined. This study examined whether anxiety in late pregnancy constituted a distinct multidimensional psychological construct using a theory-driven psychometric approach. A community-based cross-sectional study was conducted among 280 women in late pregnancy between 28 and 40 weeks of gestation. A structured self-report instrument was developed through conceptual analysis and expert review, and its latent factor structure was evaluated using confirmatory factor analysis within a structural equation modeling framework. The analysis supported a three-domain multidimensional structure encompassing childbirth-related anxiety, fetal health anxiety, and maternal mental readiness and self-confidence. The model demonstrated acceptable overall fit (χ²/df = 3.15; RMSEA = 0.088; CFI = 0.97; TLI = 0.96), with all indicators loading significantly on their respective latent dimensions (standardized loadings ≈ 0.94–1.01). These findings indicated that anxiety in late pregnancy represented a distinct multidimensional construct, supporting dimension-specific assessment in antenatal and perinatal mental health research.